2005
DOI: 10.1177/070674370505000517
|View full text |Cite
|
Sign up to set email alerts
|

Delusion of Oral Parasitosis in a Patient with Major Depressive Disorder

Abstract: A few reports of sertraline-induced akathisia and dystonia are available, but reporting on sertraline-induced Parkinsonism is negligible (1). We report a case of Parkinsonism associated with sertraline use. To our knowledge, this is the first case in the literature to highlight a possible relation between selective serotonin reuptake inhibitors (SSRIs) and lactic acid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Body orifices such as the nose, ears, mouth, anus, and the whole gastrointestinal tract are often affected (78,91,110,122,130,195,245,262), mainly in the elderly (234). DI of the eyes has been described in single cases (187,287,296,327).…”
Section: The Imaginary Pathogensmentioning
confidence: 99%
“…Body orifices such as the nose, ears, mouth, anus, and the whole gastrointestinal tract are often affected (78,91,110,122,130,195,245,262), mainly in the elderly (234). DI of the eyes has been described in single cases (187,287,296,327).…”
Section: The Imaginary Pathogensmentioning
confidence: 99%
“…Date ranges were not specified for any searches. Complete searches resulted in 42 case studies 3,531 utilised in this article, and a review of these cases was completed in April 2015 (see Table 1). Since this time, we have uncovered through repeat searches a further 64 case studies to be reviewed and reported in a later publication.…”
Section: Literature Searchmentioning
confidence: 99%
“…In responders, onset of symptom relief has occurred in 10 days to 4 weeks. [5][6][7][8][9][10][11][12][13][14] …”
Section: Case Series/reportsmentioning
confidence: 99%